Green financing and wind power energy generation: Empirical insights from China. (April 2023) - Sun, Lingyun; Yin, Jiemin; Bilal, Ahmad Raza
Abstract: The study tests the connection between green financing and wind power energy generation during the COVID-19 crisis. The study tested the relationship between the variables using the Kalman approach, Hansen technique and sensitivity analysis using matrix component factors. The findings revealed that wind power energy consumption had increased quickly in past times due to its input nature for biofuel production. However, the capability of onshore and offshore wind power production grew by 7% in COVID-19 with the role of green financing in the wind power sector. Moreover, green financing enhances the demands on wind generators and energy converters' usage and dependability by 26%. For this, a 39% increase in green financing is noticed by the research findings during the COVID-19 crisis period. Such robust study findings present the latest insights that green financing is an eminent and viable source of financing to enhance wind power energy generation. Following these, multiple research implications are also presented for the key stakeholders. Highlights: Green financing has a heterogeneous effect on wind power generation sources in China. The elasticity of green financing significantly effects the wind power energy generation. Green financing is viable sources to cover the cost of wind power energy generation and distribution. The responsiveness of the green financing depends upon the magnitude of the wind power energy generation and distribution.